“Will I Die Now?” Mystical Experiences in Individuals with COVID-19 after a Near-Death Experience - Izza Himawanti; Muhammad Faiq (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
Near-death experiences (NDEs) are closely related to emotional and spiritual dimensions, even though they are subjective. This study aims to reveal the mystical experiences of individuals suffering from COVID-19 after NDEs. This article is qualitative research with a phenomenological approach. With purposive sampling, the data were collected from individuals suffering from COVID-19 who experienced NDEs but recovered. The data were then analysed with interpretive phenomenological analysis (IPA). This study reveals that when individuals experience NDEs, they no longer see and feel their physical body but their spirit or soul. They also have mystical experiences, such as being visited and communicating with specific religious figures and even the spirits of people who had died. After NDEs, a comprehensive reconstruction occurs regarding their personal beliefs and values regarding life and death, especially their relationship with God.Contribution: This study contributes to revealing the mystical experience of people after near-death experience (NDE). This study can be a recommendation, counselling, therapy and various psychological and religious interventions for individuals who experience NDE to accept their death more easily.